2019
DOI: 10.3389/fimmu.2019.02500
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Antibody-Independent Immune Response of B Cells in Patients With Acute Dengue Infection

Abstract: Dengue is a mosquito-borne viral disease caused by dengue virus (DENV). The disease is endemic to more than 100 countries with 390 million dengue infections per year. Humoral immune responses during primary and secondary DENV infections are well-investigated. However, the impact of DENV infection on B cell subsets and their antibody-independent functions are not well-documented. Through this study, we aimed to define the distribution of B cell subsets in the acute phase of DENV infection and characterize the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…In addition, infection of α/β-T cell deficient mice with JEV results in death over a 10- to 18-day period, in contrast to wildtype mice, which can survive infection, attributable to the granular lytic function of the cells (Jain et al, 2017 ). For DENV, lower percentages of regulatory B-cell subsets are associated with a more severe disease outcome during acute infection in humans (Upasani et al, 2019 ). Mosquito salivary factors have an effect on B- and T-cell responses and the proportion of these cell populations.…”
Section: The Effect Of Saliva On the Lymphocyte Response To Arbovirusmentioning
confidence: 99%
“…In addition, infection of α/β-T cell deficient mice with JEV results in death over a 10- to 18-day period, in contrast to wildtype mice, which can survive infection, attributable to the granular lytic function of the cells (Jain et al, 2017 ). For DENV, lower percentages of regulatory B-cell subsets are associated with a more severe disease outcome during acute infection in humans (Upasani et al, 2019 ). Mosquito salivary factors have an effect on B- and T-cell responses and the proportion of these cell populations.…”
Section: The Effect Of Saliva On the Lymphocyte Response To Arbovirusmentioning
confidence: 99%
“…In patients infected with DENV, B cells show an activated phenotype leading to massive early plasmablast formation [ 8 , 11 , 51 ]. The current study demonstrates that eighty different IgM autoantibodies against complement components, coagulation factors and intracellular antigens were increased in patients infected with DENV compared to HD.…”
Section: Discussionmentioning
confidence: 99%
“…During the acute phase of infection, a rapidly expanding plasmablast population has been observed, where plasmablast frequencies are increased compared to other infectious diseases or after influenza or yellow fever vaccination [ 6 , 7 ]. In addition, frequencies of circulating plasmablast are associated to more severe dengue disease [ 8 ]. Here, DENV is capable to activate B cells directly inducing polyclonal and highly cross-reactive antibody generation after both primary and secondary infection [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Infection with dengue virus has major impacts not only on the myeloid compartment in the blood but also on lymphoid cells (16). For example, it has been shown that circulating CD19 + cells are increased in dengue patients (17,18) and that their subset distribution is significantly altered during infection (19). For example, a massive increase in the frequencies of plasmablasts and plasma cells, reaching up to 50% of circulating B cells during the acute phase of infection has been reported (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that circulating CD19 + cells are increased in dengue patients (17,18) and that their subset distribution is significantly altered during infection (19). For example, a massive increase in the frequencies of plasmablasts and plasma cells, reaching up to 50% of circulating B cells during the acute phase of infection has been reported (19,20). Moreover, enhanced B cell activation and plasma cell development have been observed in hospitalized dengue patients compared to asymptomatic infected patients (21).…”
Section: Introductionmentioning
confidence: 99%